The potential therapeutic effect of manipulating the extracellular matrix in idiopathic pulmonary fibrosis - Philp, Christopher J. (2016)
Background: Idiopathic Pulmonary Fibrosis (IPF) is a physiologically devastating disease. The debilitating nature and high mortality rates make this one of the most lethal conditions, usually associated with median time to mortality of around 3 years. Increased deposition of extracellular matrix (ECM) and fibroblast accumulation are hallmarks of idiopathic pulmonary fibrosis (IPF). We hypothesise that the ECM in IPF is structurally abnormal by virtue of aberrant cross linking and promotes fibroblast accumulation. This study examined the structure and biological activity of IPF derived ECM and how this related to the expression of ECM cross linking enzymes as well as how inhibiting Transglutaminase 2 affects active fibrosis in the murine Bleomycin model.